THE USE OF DIETARY SUPPLEMENTS IN A THE GENERAL POPULATION FROM IASI - A PILOT STUDY - Silvia Godea (Lupei); Cristina Mihaela Ghiciuc; Diana Ciubotariu; Raoul Vasile Lupușoru; Cătălina Elena Lupușoru (Romanian Dental Association for Education, 2020)
Consumption of dietary supplements and over-the counter (OTC) medication is considered as a healthy promoting activity, therefore their use increased in the past decades. Material and methods. A cross-sectional self-filled questionnaire-based study was conducted on a group of at least 100 persons over 18 years old from Iasi city. The answers were based on Likert's scales: "strongly agree / agree / neutral / disagree / strongly disagree", "yes / no" or "yes/ no / I don't know". The questionnaire had 36 questions with closed or open answers that evaluated the practices, knowledge, perceptions and attitudes of the population under study. Results. A total of 109 questionnaires were fully filled. The median age was 43 years (min 18, max 80). Approximatively two-thirds of the group were females (63 females, 58%), similar to the users group (57 females, 63%). Vitamins and minerals were commonly used. One-third of the respondents of the user group (38.8%) consume dietary supplements after self-prescription and one-third use the dietary supplements after the recommendation of a physician (28%) or pharmacist (5%). Conclusions. Almost 82% of the studied population use dietary supplements, especially vitamins and minerals, most of the used by women. The findings of our study should be interpreted bearing in mind that the study population may differ from other regions. The results should be considered as being limited to a small sample of population and place of residence.